Análise dos efeitos antimicrobianos e ecotoxicológicos de nanopartículas fúngicas de ouro sobre bactérias - Trotta, Caterina do Valle [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Gold nanoparticles (AuNPs) have attracted scientific and technological interest due to its ease of synthesis and distinctive properties attributable to its reduced size, in addition to applications such as construction of biosensors, in treatment and diagnosis of cancer, besides acting as antimicrobial agents. Physical and chemical methods are used to synthesize NPs; however, biological methods are preferred because of their ecological sources, being a green synthesis of nanoparticles (NPs) a promising and innovative field in bionanotechnology. Filamentous Fungal Bones (Ffs) are highlighted in the literature for obtaining metallic nanoparticles due to the diversity, being considered more promising. In this context, the present work aims to evaluate the antimicrobial activity of the bionanoparticle AuNP suspended and immobilized on the bacteria Escherichia coli IPT245, Pseudomonas aeruginosa IPT236 and Staphylococcus aureus IPT246 and potential toxic effects on marine microalgae Chlorella minutissima and freshwater microalgae Chlorella fusca. The AuNPs were characterized by UV-vis spectrophotometry, 'Dynamic Light Scattering’ (DLS) and Polydispersity Index (PDI) and their antimicrobial activity avaliated by Minimum Inhibitory Concentration using the pathogenic bacteria Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. The microalgae Chlorella minutissima and Chlorella fusca were used for cell density studies. In summary, the suspended AuNP showed no antibacterial activity in any concentration in which the pathogenic bacteria were exposed. In contrast, the AuNP encapsulated with chitosan-alginate exhibited antibacterial activity on the Gram-negative bacteria E. coli IPT245, and according to the results of the cell density test with the microalgae C. minutissima and C.fusca, it can be said that the use of AuNPs in aquatic environment can be considered an environmental risk, therefore the disposal of the AuNPs residues must be properly forwarded. In view of the results obtained, biosynthesis still needs to be optimized, exploring mainly factors that influence the size and time to obtain the nanomaterial in study.

As nanopartículas de ouro (AuNPs) têm atraído enorme interesse científico e tecnológico devido à sua facilidade de síntese, apresentam propriedades distintas além das decorrentes de seu tamanho reduzido, apresentando aplicações como na construção de biossensores, no tratamento e diagnóstico de câncer, além de agir como agentes antimicrobianos. Métodos químicos e físicos são usados para sintetizar NPs; no entanto, os métodos biológicos são preferidos devido às suas fontes ecológicas, sendo a síntese verde de nanopartículas (NPs) uma ferramenta promissora e inovadora na bionanotecnologia. Os fungos filamentosos (Ffs) recebem destaque na literatura pela obtenção de nanopartículas metálicas por conta da diversidade, sendo considerados os mais promissores. Nesse contexto, o presente trabalho tem como objetivo avaliar a atividade antimicrobiana da bionanopartícula AuNP em suspensão sobre as bactérias Escherichia coli IPT245, Pseudomonas aeruginosa IPT236 e Staphylococcus aureus IPT246 e potenciais efeitos tóxicos sobre microalga marinha Chlorella minutissima e microalga de água doce Chlorella fusca. A AuNP foi caracterizada por espectrofotometría UV-vis, ‘Dynamic Light Scattering’ (DLS) e Índice de polidispersão (PDI) e a atividade antimicrobiana avaliada por concentração mínima inibitória utilizando as bactérias patogênicas Escherichia coli, Pseudomonas aeruginosa e Staphylococcus aureus. As microalgas Chlorella minutissima e Chlorella fusca foram utilizadas para estudos de densidade celular. Em síntese, a AuNP em suspensão não apresentou atividade antibacteriana em nenhuma das concentrações em que as bactérias patogênicas foram expostas. Em contrapartida, a AuNP encapsulada com quitosana-alginato obteve atividade antibacteriana sobre a bactéria gram-negativa E. coli IPT245, e de acordo com os resultados do teste de densidade celular com as microalgas C. minutissima e C. fusca, pode-se dizer que o uso das AuNPs em meio aquático pode ser considerado um risco ambiental, portanto, o resíduo e descarte gerado deve ser devidamente encaminhado. Tendo em vista os resultados obtidos, a biossíntese ainda necessita ser otimizada, explorando principalmente fatores que influenciam no tamanho e tempo de obtenção do nanomaterial de estudo.
Analysis of antimicrobial and ecotoxicological effects of fungi synthesized gold nanoparticles on bacterias
Keywords: Fungo filamentoso; Escherichia coli; Chlorella sp; Nanopartícula de ouro; Nanotecnologia